Aumento de las sanciones preventivas de libertad para adolescentes infractores y la protección integral, juvenil. - Chuez Cedeño, Welington David (2014)
This legal research highlights various concerns about violations and violations to human rights in Ecuador, increasing sanctions Privatives of freedom for adolescent offenders and Integral Protection, Chapter I, Introduction, this research is composed of ises chapters structured as follows: Chapter I entitled: THE PROBLEM, within which comprises a clear and precise analysis, starting from a problematic at the global, national and local levels, with topics relevant to research in Ecuador. Chapter II, theoretical framework, in research carried out in the city of Quevedo, Los Ríos province, were prepared using texts by various writers and scholars of the right to childhood and adolescence Ecuadorians and foreigners to develop this theme. Chapter III, methodology, for the development of this legal work we have made an approach to qualitative and quantitative character in such a way, is applied in this research and work of degree of a reliable way to the bibliographic-documental, and field research. Chapter IV, analysis and interpretation of results, here all events raised by field research project. Chapter V, conclusions and recommendations, it focuses responsibly the final conclusions the research product; as well as several viable recommendations pertaining to the subject of research. Chapter VI, Proposition, we emphasize that within the Ecuadorian state to worry more in carefully monitored to make these educational measures to protect juvenile offenders who are detention.